2021
DOI: 10.1080/03069885.2021.1937515
|View full text |Cite
|
Sign up to set email alerts
|

Increasing students’ career readiness through career guidance: measuring the impact with a validated measure

Abstract: Career readiness is an important short-term outcome of career guidance activities in England. This research (1) details the development of a career readiness measure and (2) tests the relationship between career guidance interventions and career readiness among secondary school students. The measure was piloted on pupils (Study 1, N = 1508) in England taking part in a career guidance pilot programme. The instrument fitted a nine-item one-factor structure. In Study 2 (N = 2240), we found further evidence the fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 29 publications
0
12
0
2
Order By: Relevance
“…A potential intervention to consider in Mongolia is to deliver lessons and activities to support students’ post-secondary school planning and career readiness. “Career guidance describes a range of school-based interventions which seek to prepare young people for their transition to their post-secondary school lives and to empower them to be successful in their lives and careers” (Dodd et al, 2022, p. 261). In a study of English participants ages 12–18, Dodd et al (2022) found that higher levels of participation in career guidance were associated with higher levels of career readiness.…”
Section: Discussionmentioning
confidence: 99%
“…A potential intervention to consider in Mongolia is to deliver lessons and activities to support students’ post-secondary school planning and career readiness. “Career guidance describes a range of school-based interventions which seek to prepare young people for their transition to their post-secondary school lives and to empower them to be successful in their lives and careers” (Dodd et al, 2022, p. 261). In a study of English participants ages 12–18, Dodd et al (2022) found that higher levels of participation in career guidance were associated with higher levels of career readiness.…”
Section: Discussionmentioning
confidence: 99%
“…This may include the number of students attending career guidance and counselling programmes organised by schools, groups and individuals seeking counselling to deal with anxiety related to career indecision, undertaking decisions related to subject combination and career path, course of study in higher education and nature of employment. Dodd (2021) in their study observed that increased awareness and utilisation of career guidance and counselling among students improved their career decision making skills. Savickas et al (2002) also argued that by the end of adolescence, students who get sufficient career guidance and counselling were able to narrow down their career choices and attain stable career self-concept in life than their counterparts.…”
Section: Discussionmentioning
confidence: 95%
“…An empirical representation of the CEDF was constructed as the Career Education and Development Scale-Senior (CEDS-Senior). The scale's development used a similar process to the six steps recommended by Dodd et al (2021), namely: Identification of outcomes and review of existing measures; mapping of frameworks and generation of items; expert review; cognitive testing with the intended users; gathering pilot data and exploring the factor structure; and using confirmatory factor analysis (CFA) to finalize the instrument.…”
Section: Methodsmentioning
confidence: 99%
“…However, CRQ-A was developed in a country where the major educational course decision is made in Grade 9 (aged 14 years) and consequently, the key construct of career decision-making is not included in their measure. Another exception is the measure developed in the United Kingdom by Dodd et al (2021), the Student Career Readiness Index (SCRI) which is a single-factor scale based on a blend of existing career development frameworks and the CDMSES (Betz et al, 1996). They developed this single-factor measure to ascertain the impact that the career education and development programmes had as a result of the increase in career education generated by the introduction of the Gatsby Benchmarks (Dodd et al, 2021).…”
Section: Initial Development Of the Cedfmentioning
confidence: 99%